Perlindungan Hukum Pasar Tradisonal Terhadap Keberadaan Pasar Modren di Kota Yogyakarta - Heli Junggul Riadi (FH UMY, 2014)
Perlindungan Hukum Pasar Tradisonal Terhadap Keberadaan Pasar Modren di Kota Yogyakarta